Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1365-2095.2007.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacillus subtilis on growth development and survival of larvae Macrobrachium rosenbergii (de Man)

Abstract: A feeding experiment was conducted to investigate the effect of Bacillus subtilis bacterium, on larval growth and development rate of Macrobrachium rosenbergii (de Man) during February 28 to April 8, 2005 in University Putra Malaysia hatchery. Newly hatched larvae of M. rosenbergii were reared with two dietary treatments consisting of newly hatched Artemia salina nauplii with B. subtilis (108 cells ml−1), and newly hatched A. salina nauplii without B. subtilis carried out in triplicate in 60‐L aquarium (50 L−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 26 publications
(56 reference statements)
5
44
0
5
Order By: Relevance
“…These may be attributed to the possibility of higher feed intake and SGR related to treated groups (Keysami et al 2007). The recent reports on the use of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These may be attributed to the possibility of higher feed intake and SGR related to treated groups (Keysami et al 2007). The recent reports on the use of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…(Rumsey et al 2007), Bacillus sp. (Balcazar et al 2004;Meunpol et al 2003;Keysami et al 2007) and mixed cultures (Sotomayure and Balcazar 2003;Meunpol et al 2003;Salinas et al 2005;Aly et al 2008). The trials demonstrated the growth promotion of fish and crustaceans compared to control groups.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Macey & Coyne (2005), melaporkan penggunaan bakteri probiotik pada budidaya abalon. Penggunaan probiotik pada budidaya udang juga telah banyak dilaporkan, seperti pada budidaya udan g w indu (Meunp ol et al, 2 003;Vaseeharan et al, 2004;Lio-Po et al, 2005;Gunarto et al, 2006aGunarto et al, ,2006bVijayan et al, 2006), budidaya udang Penaeus chinensis (Li et al, 2006), budidaya udang vanamei (udang putih) (Nejad et al, 2006), budidaya udang galah (Keysami et al, 2007), pemeliharaan larva udang (Decamp et al, 2008), dan budidaya udang stylorostris (udang putih) (Castex et al, 2008).…”
Section: Pendahuluanunclassified